Draft Representation of Women in Candidate Determination in Elections Member of the People's Representative Council of the Republic of Indonesia Realize Gender Equality - Edeltrudis Calasansia Murni; Didik Suhariyanto; Ismail Ismail (SEAN Institute, 2026)
Women's representation in politics is a crucial issue in realizing gender equality and inclusive democracy. Regulations through Law Number 7 of 2017 concerning Elections and General Election Commission Regulations (PKPU) have stipulated the obligation of political parties to include at least 30% women in the list of legislative candidates in each constituency. However, electoral political practices show that there is a discrepancy in the formulation of representation, both in terms of distribution and placement of female candidates on non-strategic lists. Legal vacuums arise when quota provisions are not consistently enforced, so that the principles of substantive justice and the protection of women's political rights are weakened. The purpose of this research is to analyze the formulation and enforcement of women's representation law in the determination of candidates for members of the House of Representatives of the Republic of Indonesia based on PKPU in order to realize gender equality in elections. The research method used is a normative juridical method with legislative, case, and conceptual approaches. The results of the study show that women's representation in the determination of candidates for members of the House of Representatives of the Republic of Indonesia has not been fully realized in accordance with regulations. Data from the 2024 election shows that women only obtained 22.1% of the seats in the House of Representatives, still below the 30% quota target. This inconsistency illustrates weak institutional commitment, legal uncertainty, and structural bias in the political system. The conclusion of this research is that although regulations have regulated the quota of women's representation, weak law enforcement and institutional commitment have caused gender equality in elections to not be achieved substantively.